ESTIMATION OF THE ECONOMIC LOSSES POTENTIAL DUE TO UNDERWEIGHT TODDLERS IN INDONESIA IN 2013 - Brigitte Sarah Renyoet (Universitas Airlangga, 2021)
Millions of children and adolescents in Indonesia today still show a high number of premature death in children who are moderately malnourished and severely malnourished. The research objective was to calculate the estimated economic losses potential due to underweight among toddlers in Indonesia. This was a descriptive research by analyzing secondary data of nutritional status and socio-economic indicators in 2013 from the Indonesian Ministry of Health and Central Statistical Agency. The formula to calculate potential economic loss is based on Konig’s formula (1995) and the correction factor from research by Horton (1999). The results showed that the average economic loss in 32 provinces in Indonesia is approximately IDR 93 billion – IDR 417 billion, which seen from the GRDP percentage, the economic loss due to a decrease in productivity amounted to 2% and 9% or about 0.1–0.7% of the average GRDP of the provinces in Indonesia. Nationally, economic losses due to low productivity in underweight toddlers reach IDR 3,054 billion – IDR 13,746 billion (0.04–0.2%) of Indonesia’s total GDP. The results of this study are expected to show that the importance of this issue was handled and can assist the government in planning for health and nutrition programs targeted to human resources in Indonesia qualifi ed and productive.